BRIDGING TO ANOTHER DIMENSION: THE RELATIONAL SYSTEM OF SHAMANISM AND RELIGIOUS ENCOUNTER AMONGST THE TEMIAR SENOI OF MALAYA - Riza Saputra; Husnul Khotimah (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2021)
This paper aims at finding the relational system, religious encounter, and modernity of the Temiar community in Malaysia. The form of this research has focused on literature research (library research) by using literature as a source of research. The method used is an analysis of documents by conducting content analysis. This within-case analysis is followed by a thematic analysis across the case. The data patterns emerging from the within-case and cross-case analysis of theme, the information of Temiar’s world view is compared from several documents. Having discussed the relational systems in shamanic society and religious encounters and modernity amongst Temiar, this paper concludes that: Firstly. Shaman creates the cultural experience in the inter-subjective space of the ritual as the flow of the spirit guide through the healing ritual. The shaman is the spirit medium, a person who can receive songs from the spirit guide during dreams. Secondly, singing and dancing is an activity that in itself bridges the gulf between the physical world and the metaphysical. Thirdly, Temiars have begun to incorporate representations of varying spirit entities associated with religious conversion and modernization into their cosmology.